WHAT MOTIVATES PRE-SERVICE TEACHERS TO BECOME TEACHERS AND THEIR PERSPECTIVES OF ENGLISH TEACHING AS A CAREER OPTION - Tustiawati, I. A. Mela (TEFLIN Journal, 2017)
Teaching motivation issues are well-researched in several countries. However, these issues have been rarely investigated in the Indonesian context. This study investigated motivational factors that influence pre-service teachers to enter English teacher training and their perspectives of English teaching as a career option. It comprised a survey of 140 pre-service teachers from a teacher training institution in Bali and two semi-structured group interviews. The results suggest that the participants are more influenced by intrinsic and altruistic factors than extrinsic factors. These findings contradict earlier studies of teacher motivation in developing countries and what is generally believed in Indonesia. Moreover, the development of the tourism industry in Bali seems to have a great impact on the participants’ perspectives of English teaching in Bali in particular and in Indonesia in general. Most of those surveyed held positive views of the development of English teaching as a career option. Finally the study suggested implications and recommendations for additional studies within the Indonesian context.